Vom Waldheros zum Sonnenheros, Die Entwicklung der Erzählungen von Samson und Herakles - Jagiełło, Mieszek (Polskie Towarzystwo Filologiczne, 2018)
Samson from the Book of Judges has been compared to Heracles on many occasions. The following paper suggests a new point of view for the subject: while Samson’s solar aspect seems almost undeniable, Heracles’ connection to the deified sun needs reconsideration. Originally, he might have rather been some kind of a sylvan hero. Especially Homer’s description of the mighty demigod points towards this conclusion, but also his dodekathlos provide some evidence. The author explores this hypothesis and proposes a chronology for the evolution of the myth.
Keywords: Samson; Herakles